2005
DOI: 10.1096/fj.04-3329fje
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Bax dimerization promotes its translocation to mitochondria independently of apoptosis

Abstract: Bax is a cytosolic protein, which in response to stressing apoptotic stimuli, is activated and translocates to mitochondria, thus initiating the intrinsic apoptotic pathway. In spite of many studies and the importance of the issue, the molecular mechanisms that trigger Bax translocation are still obscure. We show by computer simulation that the two cysteine residues of Bax may form disulfide bridges, producing conformational changes that favor Bax translocation. Oxidative, nonapoptogenic treatments produce an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 72 publications
5
113
0
Order By: Relevance
“…Then, data suggest that Bax C-terminal Hα9 could participate to the pore formation [40], maybe through its polar residues. Finally, a study reported the possible formation of intermolecular disulfide bonds involving Bax C62 and C126 residues [56]. Bax mitochondrial localisation may create a favourable environment to the formation of such bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Then, data suggest that Bax C-terminal Hα9 could participate to the pore formation [40], maybe through its polar residues. Finally, a study reported the possible formation of intermolecular disulfide bonds involving Bax C62 and C126 residues [56]. Bax mitochondrial localisation may create a favourable environment to the formation of such bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Besides altering their abundance, melatonin could alter Bax and Bcl-2 activity in other ways. Oxidative alterations cause Bax disulfide dimerization, and the resulting conformational changes are sufficient for its translocation to mitochondria independently of apoptosis [116]. However, melatonin maintains Bax in a monomeric state within mitochondria [108].…”
Section: Page 9 Of 29mentioning
confidence: 99%
“…Both cysteines are exposed and potentially reactive to form disulfide bridges for either homo-or hetero-dimerization (D'Alessio et al, 2005); in silico models propose that homodimers via disulfide bonds between cysteine 62 and cysteine 126 expose the hydrophobic alpha helix 9 promoting membrane insertion (D'Alessio et al, 2005).…”
Section: Critical Amino Acid Residuesmentioning
confidence: 99%
“…It was shown that after treatment with H 2 O 2 at low concentrations, or after glutathione depletion in U937 and HepG2 cells, cytochrome c is released in the absence of apoptosis (Ghibelli et al, 1999); at the same time, Bax translocates to mitochondria, and undergo dimerization, as detected in non-reducing but denaturing electrophoresis (SDS-PAGE) (D'Alessio et al, 2005). Cell-free oxidation of cytosolic extracts with H 2 O 2 leads to disulfide dimerization.…”
Section: Bax As a Sensor Of Physico-chemical Alterationsmentioning
confidence: 99%